Evaluation of fibrous feed ingredients alternatives to oat hulls as a source of feed structure in broiler diets - Reza Akbari Moghaddam Kakhki; Alberto Navarro-Villa; Jon de los Mozos; Sonja de Vries; Ana Isabel García-Ruiz (Poultry Science, 2024)
ABSTRACT: This study aimed to evaluate several fibrous feed ingredients as potential substitutes for oat hulls (OH), assessing their efficacy in providing structural integrity to broiler feeds. A total of 4,160 day-old male Ross-308 broilers were allocated to eight dietary treatments, including a control group (CON) without additional fiber supplementation and 7 diets where 3% of the wheat content was replaced by either OH, soy hulls (SH), beet pulp (BP), carob bean (CB), wheat straw (WS), rice hulls (RH), or wheat bran (WB). The experimental design followed a complete randomized block design with 10 pens per treatment and 52 birds each. Growth performance and gut development indices were monitored, and the coefficients of total tract apparent retention (CTTAR) of nutrients were measured at 28 d. The OH improved feed conversion ratio (FCR) during the entire growth period (1–36 d) compared to the CON, SH, CB, WS, RH, and WB (P < 0.05). Conversely, BP diets reduced the final BW and ADFI compared to OH (P < 0.05) but were not different from the CON (P > 0.05). However, the FCR in birds fed with BP was similar to OH but lower than the CON group. In addition, BP-fed birds had higher CTTAR of ether extract and non-starch polysaccharides and relative weight of empty proventriculus and gizzard to BW at 14 and 28 d compared to CON. The WS, RH, and WB yielded similar final BW to OH and CON but higher FCR (P < 0.05). The CB, on the other hand, resulted in the highest FCR when contrasted with the other substitutes and CON (P < 0.05). Finding an alternative to OH with comparable benefits remains a challenge, with WS, RH, and WB showing similar final BW but inferior FCR to OH, and BP showing similar FCR but lower BW and ADFI.